2017
DOI: 10.1016/j.atherosclerosis.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin and diet interventions on atherosclerotic plaque inflammation and [18F]FDG uptake in Ldlr−/−Apob mice

Abstract: Atorvastatin therapy did not show cholesterol-independent effects on inflammation in atherosclerotic lesions in LdlrApob mice, as determined by histology and [F]FDG PET, whereas a cholesterol-lowering diet intervention was effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Furthermore, we have extended the previous studies by evaluating 18 F-FDG uptake in the aorta. 18 F-FDG-PET can be used to quantify inflammation in atherosclerotic lesions in a non-invasive and reproducible manner, because increases in 18 F-FDG accumulation reflect higher glucose consumption by inflammatory cells [11,21,25,26]. Previous studies indicate that a metabolic marker like 18 F-FDG uptake is sensitive to changes caused by short-term interventions, irrespective of alterations in plaque burden [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have extended the previous studies by evaluating 18 F-FDG uptake in the aorta. 18 F-FDG-PET can be used to quantify inflammation in atherosclerotic lesions in a non-invasive and reproducible manner, because increases in 18 F-FDG accumulation reflect higher glucose consumption by inflammatory cells [11,21,25,26]. Previous studies indicate that a metabolic marker like 18 F-FDG uptake is sensitive to changes caused by short-term interventions, irrespective of alterations in plaque burden [25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 18 F-FDG PET/CT imaging has demonstrated the ability to detect the effectiveness of various statin dosing regimens at reducing plaque inflammation [16••, 19]. While 18 F-FDG PET/CT imaging has demonstrated utility for predicting cardiovascular events and tracking therapy in patients, vascular 18 F-FDG uptake has also been shown to be significantly elevated in patients with elevated lipoprotein(a) levels [23] and significantly correlate with circulating levels of myeloperoxidase [18] and total plasma cholesterol [21]. Recent work by Cocker et al [24] further revealed that 18 F-FDG uptake specifically represents a non-invasive surrogate marker of macrophage and leukocyte infiltration by demonstrating that 18 F-FDG uptake in carotid artery endarterectomy specimens significantly correlated with both CD68 macrophage expression and CD45 leukocyte expression.…”
Section: Radionuclide Imaging Of Vascular Inflammationmentioning
confidence: 99%
“…When analyzed with in vivo PET/CT scan and ex vivo gamma counting of excised aorta in hypercholesterolemic mice deficient in LDL receptor and expressing only apolipoprotein B-100, 18 F-FDG uptake in the aorta was significantly lowered by a cholesterol-lowering diet [ 93 ]. At the same time, this dietary intervention effectively reduced plaque burden and macrophage count within atherosclerotic lesions on aortic histopathology [ 93 ].…”
Section: Improvement In Vascular Inflammation Assessed By Positronmentioning
confidence: 99%
“…When analyzed with in vivo PET/CT scan and ex vivo gamma counting of excised aorta in hypercholesterolemic mice deficient in LDL receptor and expressing only apolipoprotein B-100, 18 F-FDG uptake in the aorta was significantly lowered by a cholesterol-lowering diet [ 93 ]. At the same time, this dietary intervention effectively reduced plaque burden and macrophage count within atherosclerotic lesions on aortic histopathology [ 93 ]. Notably in a clinical setting, Lee et al [ 56 ] reported that atherogenic risk reduction through lifestyle intervention reversed vascular 18 F-FDG uptake in PET/CT in 60 healthy adults, and the extent of reduction in the 18 F-FDG index correlated well with elevations in plasma HDL cholesterol levels [ 56 ].…”
Section: Improvement In Vascular Inflammation Assessed By Positronmentioning
confidence: 99%